1972
DOI: 10.1073/pnas.69.10.2890
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Aggregation of Cytoplasmic Microtubule Subunits

Abstract: The colchicine-binding protein in porcinebrain tissue is a dimer of molecular weight 110,000 that is believed to be the subunit of neuronal microtubules. Conditions are established under which the dimers aggregate with reproducible kinetics. This aggregation reaction, which is monitored by development of turbidity, has the following characteristics: (a) Colchicine inhibits development of turbidity; (b) the reaction inhibited by colchicine is reversed by long-wave ultraviolet irradiation; (c) the aggregation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…The occurrence of rat-brain and in vitro-synthesized NB tubulin in the 100,000 X g pellet obtained from the reaction mixture is in agreement with recent studies (30) which indicated that, at 37°in the presence of 1 mM GTP and salt (conditions similar to those in our protein synthesis reactions), soluble tubulin aggregates and can be pelleted even by a low-speed centrifugation (30,000 X g, 30 min). In an attempt to separate Proc.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The occurrence of rat-brain and in vitro-synthesized NB tubulin in the 100,000 X g pellet obtained from the reaction mixture is in agreement with recent studies (30) which indicated that, at 37°in the presence of 1 mM GTP and salt (conditions similar to those in our protein synthesis reactions), soluble tubulin aggregates and can be pelleted even by a low-speed centrifugation (30,000 X g, 30 min). In an attempt to separate Proc.…”
Section: Resultssupporting
confidence: 75%
“…The identification of '4C-labeled tubulin synthesized was based on the following criteria: (i) it was precipitable by an antiserum against tubulin; (ii) it formed aggregates, as did the ratbrain tubulin, under the protein synthesis incubation conditions which are similar to those used for in vitro assembly of soluble tubulin (30); (iii) as described for other tubulin molecules (31), the aggregation of the in vitro synthesized 14C. labeled tubulin was specifically enhanced by treatment with 4 M glycerol in "assembly buffer"; (iv) it has a molecular weight of 53,000 which is in agreement with published molecular weight data, and (v) the "4C-labeled tubulin comigrated on SDS PA gels with native NB tubulin which had been shown to bind tolchicine and also with the native rat brain tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that these alkaloids bind to the microtubular protein subunit (8), but do not interact with polymerized microtubules (25,26). In addition, colchicine prevents the polymerization of microtubular protein (27,28). If the cellular action of vasopressin promotes polymerization of microtubular protein, colchicine and vinblastine may prevent the action of vasopressin by binding to microtubular protein, thereby interfering with microtubule formation.…”
Section: Discussionmentioning
confidence: 99%
“…If reassociation of the CBP assembly occurred more slowly than cap formation after returning to 370, cap formation would be expected. Cap formation occurs in minutes (1,2), whereas there is some evidence that microtubular reassembly can take as long as hours (22 (24) found that receptors mediating transport were not affected by the process of phagocytosis and inferred that the two functions were topographically separate. After treatment of the cells with colchicine, however, phagocytosis led to "internalization" of the transport receptors, possibly as a result of their conversion to the F state.…”
Section: A Model For Receptor-cytoplasmic Interactionsmentioning
confidence: 99%